Impact of the meaningful use incentive program on electronic health record adoption by US children's hospitals. (8th March 2015) - Nakamura, Mari M.; Harper, Marvin B.; Castro, Allan V.; Yu, Feliciano B.; Jha, Ashish K.
Abstract: Objective We determined adoption rates of pediatric-oriented electronic health record (EHR) features by US children's hospitals and assessed perceptions regarding the suitability of commercial EHRs for pediatric care and the influence of the meaningful use incentive program on implementation of pediatric-oriented features. Materials and Methods We surveyed members of the Children's Hospital Association. We measured adoption of 19 pediatric-oriented features and asked whether commercial EHRs include key pediatric-focused capabilities. We inquired about the meaningful use program's relevance to pediatrics and its influence on EHR implementation priorities. Results Of 164 general acute care children's hospitals, 100 (61%) responded to the survey. Rates of comprehensive (across all pediatric units) adoption ranged from 37% (age-, gender-, and weight-adjusted blood pressure percentiles and immunization contraindication warnings) to 87% (age in appropriate units). Implementation rates for several features varied significantly by children's hospital type. Nearly 60% of hospitals reported having EHRs that do not contain all features essential for high-quality care. A majority of hospitals indicated that the meaningful use program has had no effect on their adoption of pediatric features, while 26% said they have delayed or forgone incorporation of such features because of the program. Conclusions Children's hospitals are implementing pediatric-focused features, but a sizable proportion still finds their systems suboptimal for pediatric care. The meaningful use incentive program is failing to promote and in some cases delaying uptake of pediatric-oriented features.